Formas de participação de crianças do primeiro ciclo do ensino fundamental em seus contextos familiares - Kassiane dos Santos Oliveira (2022)
In this research our main goal is to understand and analyze all the phenomenon related to children aged six and seven, students from the public municipal network of the Belo Horizonte city. The related children are inserted in the first cycle of Elementary School which is how education is applied in Brazil and we are going to understand their ways of participating in their family contexts. The relationship between family and child is the purpose of studies in many fields of knowledge: Sociology of the Family, Sociology of Education, Psychology and also the medical field. But the child's perspective on his own existence and the relationship established with the world around him are both recent and without a profound investigation so far. The understanding of the child as a subject capable of learning and talking about the relationships surrounding him is one of the research bases of the Sociology of Childhood and this field of studying is the root of this investigation. As a matter of fact, we consider the multidimensional aspects of childhood, we strongly believe that is necessary to evolve a research that establishes a dialogue between even deeper studies and other researches in the Sociology of Education, Sociology of Childhood and studies on the contemporary family connected in areas such as Psychology, Anthropology and Sociology. Along this investigation, we considered important to engage on the following specific objectives that were established this way: Learn and analyze the meanings that children attribute to the family; Understand the configuration of the family from the child's perspective; Identify the place that the child attributes to the family; Understand the children's perceptions about of the family-school relationship; Comprehend the perspective of adult family members on the child's place in the family; With these objectives in mind, we developed a qualitative research, using different methods for data construction based on: observation at school, questionnaire sent to families, visits to the homes of five selected children and interviews. Those semi-structured interviews were conducted with those responsible for the children in their homes, with the children (individually and in groups at school or at home) and with their teachers at school. We present the collaborating children of our research and all the results and analysis of their ways of participation in the core of their families and how they acted in the mediation of the family-school relationship. As an important result, we realized that the concept of children's participation is a concept under construction in the Sociology of Childhood and actually allows a huge vastitude of interpretations. We identified in our research, as well, that the children participate by collaborating, influencing, being submissive and, also resisting within the contexts in which they are inserted. Either it was possible of pointing out their forms of participation in the construction of this research. We consider that the child's participation is recognizable and mediated by intragenerational and intergenerational relationships, regardless of the authorization of adults, but, at the same time, potentiated or restricted by them.